Management of non-syndromic craniosynostoses in France in 2015: A national survey. Issue 4 (April 2019) - Prevost, Raphaëlle; Keribin, Pierre; Batut, Claire; Guichard, Benjamin; Ambroise, Béatrice; Bohra, Alin; Benateau, Hervé; Veyssiere, Alexis
Abstract: Purpose: Craniosynostoses are managed by surgical and anaesthetic teams in specialist centres. Despite the availability of international guidelines, the perioperative management of craniosynostoses remains highly variable between centres. The aim of our study was to describe the different protocols for the management of non-syndromic craniosynostoses in France in 2015. Materials and methods: This descriptive study consisted of a survey about the protocols of pre-operative, per-operative and post-operative management of craniosynostoses. The survey was sent to the departments in French university hospitals that perform this surgery. Results: Nineteen departments out of twenty replied to the survey. Sixteen departments organised multi-disciplinary meetings. The most frequent preoperative imaging requested was a Computed Tomography. More than half of the centres organised a follow-up until early adulthood. Conclusion: This study showed a great variability in the management of craniosynostoses. A recommendation from the study is to establish a scientific committee of practitioners in order to establish a standardised protocol. In addition, this study showed the need to create a specific section in the French rare diseases database (CeMaRa) for craniosynostoses.